Oral Contraceptives as risk factors for cervical intraepithelial neoplasia - WANI, PARAS; AHMAD, MASHKOOR; M J, SIDDIQUE; WANI, GAZANFER (The Indian Journal of Animal Reproduction, 2007)
A Clinic initiated community oriented cross sectional study on, "A Study of efficacy of VIA Technique inScreening of Carcinoma of cervix in Situ" was conducted by department Preventive and Social Medicine, J amiaHamdard, New Delhi. Analysis of positive Pap smears and VIA (Visual inspection with acetic acid) with use oforal contraceptives was done using chi square test at degree of freedom I and C.l 95%. Probability of positive Papsmears and VIA in subjects with use of oral Contraceptive practices was more.
Keywords: Cervical cancer; Contraceptives; Risk